Effect of processing method on physico-chemical and functional properties of two fonio (Digitaria exilis) landraces - Ballogou, V.Y.; Sagbo, F.S.; Soumanou, M.M.; Manful, J.T.; Toukourou, F.; Hounhouigan, Joseph D. (Springer, 2015)
In West Africa, landraces or local varieties of fonio are processed into many products by women using small processing units and marketed locally as well as exported to Europe and the United States. The objective of this study was to evaluate the effect of processing methods, namely parboiling, precooking and roasting on the physico-chemical and functional properties of two mainly preferred fonio landraces (Iporhouwan and Namba) by consumers. Results showed that the physico-chemical characteristics and most functional properties were significantly (P < 0.0001) affected by the processing methods. The lowest brightness (L*) values were obtained for parboiled fonio for the two landraces. However, parboiled fonio presented the best biochemical composition as compared to the dehusked, milled, precooked and roasted fonio samples. The protein contents of parboiled fonio samples were 6.06 % and 7.24 % for Iporhouwan and Namba landraces respectively. The values of peak viscosity, trough viscosity, breakdown, final viscosity and setback, were significantly higher for dehusked and milled fonio than for precooked, parboiled and roasted fonio with respect to both landraces. The milled fonio showed highest peak viscosity (2,668.5 cP) which was similar for the both tested landraces.